Analyzing the Impact of Quality of Public Governance on the Market Value of Companies Listed on the Amman Stock Exchange - Qwader, Amjad S. (International Journal of Economics and Financial Issues, 2024)
This study aimed to examine the impact of public governance quality on the market value of companies listed on the Amman Stock Exchange from 2002 to 2021. The study utilized the Autoregressive Distributed Lag (ARDL) model to analyze slow-moving distributed time series. The findings indicated a significant and positive correlation between various indicators of quality of public governance, such as voting and accountability, political stability and absence of violence, and organizational quality, with the market value of the listed companies. These results align with economic theory assumptions. However, in terms of Monetary freedom, another important indicator of the quality of public governance, the study found no statistically significant relationship with the market value of the listed companies at a significant level. This observation may be attributed to the government’s limited capacity to manage the country’s public financial resources efficiently and effectively, particularly regarding transparent and responsible administration of taxation, debt, and government expenditure.